2013
DOI: 10.12816/0001523
|View full text |Cite
|
Sign up to set email alerts
|

On the Factors Affecting H-Bonding : A CCSD(T) // B3LYP Study on Malonaldehyde Cation-Radical

Abstract: Among the factors that may affect H-bond strength, the effect of the molecular ionization has not received any considerable attention. Here, malonaldehyde and its cation-radical as models were studied using DFT (B3LYP) and ab-initio theories (HF, MP2, and CCSD(T)). Based on establishing a comparison with the CCSD(T)/CBS energy barrier (from literature), we have found that the CCSD(T)/D95(d,p)//B3LYP/6-31G(d,p) computational protocol can be used as a reference for evaluating performance of the B3LYP and the MP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The nature of stimuli-2 depends on the operating temperature. A support to the values of the proton transfer activation energies comes from the CCSD(T)/D95(d,p)//B3LYP/6-31G(d,p) and QCISD(T)/D95(d,p)//B3LYP/6-31G(d,p) protocols, as recommended earlier [ 14 , 18 ]. In a previous work, we demonstrated that, for a specific molecular system, tautomerism is a controllable process [ 32 ].…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…The nature of stimuli-2 depends on the operating temperature. A support to the values of the proton transfer activation energies comes from the CCSD(T)/D95(d,p)//B3LYP/6-31G(d,p) and QCISD(T)/D95(d,p)//B3LYP/6-31G(d,p) protocols, as recommended earlier [ 14 , 18 ]. In a previous work, we demonstrated that, for a specific molecular system, tautomerism is a controllable process [ 32 ].…”
Section: Resultsmentioning
confidence: 63%
“…The availability of this value allows searching for less demanding alternative methods. Previously, we found that both B3LYP/6-31++G(3df,3pd) and MP2/6-31++G(3df,3pd) protocols fail in predicting the proton transfer activation energy of malonaldehyde [ 18 ]. Table 1 presents the results of various basis set types along with the MP4(SDTQ) method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Gaussian 03 29 was used for all the calculations. The B3LYP/6-31G(d,p)-SDD protocol was employed as recommended earlier [30][31][32] for the geometry optimization and the frequency calculations. The B3LYP functional is composed of the Becke three parameter exchange functional 33 , the non-local correlation provided by Lee, Yang, and Parr (LYP) 34,35 , and local correlation functional (III) developed by Vosko, Wilk, and Nusair (VWN) 36 .…”
Section: Computational Methodmentioning
confidence: 99%